New Salicylanilide-Hg(II) complexes with phosphine ligands, Synthesis and spectroscopic investigation - Mohammed E. A. Al-Doori; Ahmed S. M. Al-Janabi (Tikrit Journal of Pure Science, 2019)
A new complex of the type [Hg(k2-Saln)2] (1) was prepared from the reaction of mercury acetate and salicylanilide (HSaln) in (1:2) molar ratio EtOH as a solvent with presence an Et3N as a base. Treatment of complex (1) with diphosphine {where diphos: dppe, dppp, dppb dppf and dppmS2} in 1:1) (complex: diphos) molar ratio afforded a complexes of the types [Hg(k1-Saln)2(diphos)] (2-6),where as a complexes of the types [Hg(k1-Saln)2(phos)2] (7,8) when treatment of complex(1) with two moles of monophosphine (PPh3 or SPPh3). The prepared complexes were fully characterization by many technical such as elemental analysis, molar conductivity, infrared spectroscopy, and nuclear magnetic resonance (1H and 31P). In complex (1) the (Saln-) was bonded as bidentate chelating ligand through the oxygen atoms of the carbonyl and deprotonated hydroxyl group, whereas bonded as monodentate ligand through the oxygen atom of deprotonated hydroxyl group in all other complexes (2-8). The geometry of the complexes (1-8) is a tetrahedral around the mercury (II) ion.